Bioactive phytochemicals in wheat: Extraction, analysis, processing, and functional properties. (October 2015) - Luthria, Devanand L.; Lu, Yingjian; John, K.M. Maria
Abstract: Whole wheat provides a rich source of bioactive phytochemicals namely, phenolic acids, carotenoids, tocopherols, alkylresorcinols, benzoxazinoids, phytosterols, and lignans. This review provides information on the distribution, extractability, analysis, and functional properties of bioactive phytochemicals present in wheat. Understanding the impact of processing on wheat phytochemicals allows us to develop improved processes with higher retention of bioactive compounds in processed wheat foods. Details of extraction, analytical methodologies and processing effects on bioactive phytochemicals in wheat are presented in tabulated form.